ADMINISTRASI DAN MANAJEMEN PENDIDIKAN DALAM PERSPEKTIF OTONOMI DAERAH - Tolla, Ismail (Eklektika, 2013)
Abstract : The implementation of Law No. 22 in 1999 on Regional Government which marks the start of a government decentralized system in the sense of autonomy paradigm gives impact to the administration and management of education. Centralized management of the education authority shifted to decentralized (autonomous regions). The concept of paradigm changes in administration and management education that is ideal for regional autonomy based education governance, namely: (i) self-reliance and empowerment of local communities without compromising national mission within the national system of education managemen. (ii) the democratization of education, the education of, by, and for the interests of the region in the context of local, national, and global. (iii) the principle of "management by vision" or MBS. (iv) management mechanisms which education oriented to regional characteristics, the ability of the region, and area requirements. (v) Direct cost, is borne by the government more and indirect costs (indirec cost) should be examined in-depth in the practice of education, borne by the public more (students and parents.